MANAJEMEN RISIKO PENUMPANG KAPAL PT (PERSERO) PELAYARAN NASIONAL INDONESIA CABANG TANJUNG PRIOK JAKARTA - David Sirait; Refri Doni Eka Putra; Yahya Kuncoro (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT (Persero) Pelayaran Nasional Indonesia is a company that provides inter-islands sea transport services covering transportation of passengers and loads. The risk problems that frequently happen in passenger ships are ship fire, the lack of safety tools, and passengers’ small awareness of dangerous goods. The solutions that taken by the company are: (1) Company allocates budget to buy new ships (2) Provides more safety tool (3) Explains the passengers about dangerous goods by using photos and videos.